أثر جائحة كورونا على قلق الامتحان لدى تلاميذ السنة الثالثة ثانوي - زيتوني, أمال; حنيش, فطيمة (University of Eloued جامعة الوادي, 2021)
الملخص: تعالج الدراسة الحالية موضوع أثر جائحة كورونا على قلق الامتحان لدى تلاميذ السنة الثالثة الثانوي ببعض ثانويات ولاية الوادي خلال الموسم الجامعي 2020/2021 . اعتمدت الدراسة على المنهج الوصفي المقارن, وذلك باستخدام مقياس قلق الامتحان ل (غربي عبد الناصر) الذي تم التأكد من خصائصه السيكومترية(الصدق, الثبات ) على عينة قوامها 37تلميذا وتلميذة , تم اختيارهم بطريقة صدفية(عرضية ). تم تطبيق الأدوات في صورتها النهائية على عينة عرضية تتكون من (83) فردا،وبعد جمع البيانات وتبويبها،تم معالجتها بالاستعانة بـ الحزمة الإحصائية للعلوم الاجتماعية ، توصلت الدراسة للنتائج التالية: وجود فروق ذات دلالة إحصائية في قلق الامتحان (قلق الاستعداد)لدى تلاميذ السنة الثالثة ثانوي تعزى لمتغير التأثر بجائحة كورونا. وجود فروق ذات دلالة إحصائية في قلق الامتحان (قلق الأداء) لدى تلاميذ السنة الثالثة ثانوي تعزى لمتغير التأثر بجائحة كورونا. وجود فروق ذات دلالة إحصائية في قلق الامتحان(قلق انتظار نتيجة) لدى تلاميذ السنة الثالثة ثانوي تعزى لمتغير التأثر بجائحة كورونا توجد فروق ذات دلالة إحصائية في قلق الامتحان لدى الكلي لدى تلاميذ السنة الثالثة ثانوي تعزى لمتغير التأثر بجائحة كورونا. Résumé :فرنسية أو انجلزية The study investigates the impact of the Corona pandemic on exam anxiety on third-year high-school students in some high schools in El Oued state during the academic year 2020/2021. The study relied on the comparative descriptive approach, using GharbiAbdelNacer's anxiety scale, whose psychometric properties (honesty, persistence) were confirmed on a sample of 37 pupils, selected in a coincidental (accidental) manner. Then applied the tools in their final form to a transverse sample consisting of (83) individuals. After collecting, classifying, and processing the data using the Statistical Package of Social Sciences. The study reached the following results: - There are statistically significant differences in exam anxiety (readiness anxiety) among third-year high-school students due to a variant of the Corona pandemic. - There are statistically significant differences in exam anxiety (performance anxiety) among third-year high-school students due to a variant of the Corona pandemic. -There are statistically significant differences in exam anxiety (result-waiting anxiety) among third-year high-school students due to a variant of the Corona pandemic. - There are statistically significant differences in total examination anxiety among third-year high-school students due to a variant of the Corona pandemic
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: قلق الإمتحان، l'anxiété liée aux examens, exam anxiety; كورونا، corona; كوفيد 19، Covid 19